Analysis of Hardness Level and pH of Drilled Well Water in Semin Village, Semin District, Gunungkidul Regency - Qurota A'yun; Nur Rokhimah Hanik; Ratna Dewi Eskundari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Water quality must be maintained so that it remains beneficial to humans and other living things, as a means of improving public health. The requirements for clean water quality have been regulated in Permenkes No. 416 of 1990 concerning Requirements and Supervision of Water Quality. The purpose of this study was to analyze water quality with hardness and pH parameters for water hygiene and sanitation used by the people of Semin village, Semin district, Gunungkidul district. The test results showed that the highest hardness level was found in sample C3 which was 228.86 mg/L and the lowest hardness level was found in sample A2 which was 89.55 mg/L. The highest pH test results were found in sample D3, which was 8.1, while the lowest pH level was found in sample A2, which was 6.5. Based on the test results, water from drilled wells in Semin village, Semin sub-district, Gunungkidul regency, is still suitable for use for hygiene and sanitation purposes.